2023
DOI: 10.1002/jmv.28833
|View full text |Cite
|
Sign up to set email alerts
|

New‐onset type 1 diabetes in children and adolescents as postacute sequelae of SARS‐CoV‐2 infection: A systematic review and meta‐analysis of cohort studies

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in children and adolescents may increase risk for a variety of post-acute sequelae including new-onset type 1 diabetes mellitus (T1DM). Therefore, this meta-analysis aims to estimate the risk of developing new-onset type 1 diabetes in children and adolescents as post-acute sequelae of SARS-CoV-2 infection. PubMed/MEDLINE, CENTRAL, and EMBASE were systematically searched up to March 20, 2023. A systematic review and subsequent meta-analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Furthermore, Bellia et al’s [ 12 ] focus on the prevalence, rather than the incidence, of new-onset diabetes further narrows the scope of the study and limits its applicability in understanding the full extent of diabetes burden in patients with long COVID. The study conducted by Rahmati et al [ 14 ] is notable for its inclusion of both acute and patients with long COVID, potentially obscuring the unique risks and outcomes associated with the prolonged phase of COVID-19. The study by Banerjee et al [ 11 ] comprised a small number of studies (n=7), potentially constraining the statistical power of the subgroup analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Bellia et al’s [ 12 ] focus on the prevalence, rather than the incidence, of new-onset diabetes further narrows the scope of the study and limits its applicability in understanding the full extent of diabetes burden in patients with long COVID. The study conducted by Rahmati et al [ 14 ] is notable for its inclusion of both acute and patients with long COVID, potentially obscuring the unique risks and outcomes associated with the prolonged phase of COVID-19. The study by Banerjee et al [ 11 ] comprised a small number of studies (n=7), potentially constraining the statistical power of the subgroup analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews examining the incidence and excess risk of new-onset diabetes in patients with long COVID (compared to individuals without COVID-19) are subject to several limitations. These limitations include the inclusion of new-onset diabetes cases that occurred during both the acute and post–COVID-19 phases [ 14 ], a small number of studies included in the meta-analysis [ 11 , 14 , 15 ], reliance solely on a single definition for COVID-19 diagnosis (such as the International Classification of Diseases, Tenth Revision [ ICD-10 ] codes) [ 16 ], the absence of meta-analysis [ 13 ], and a focus limited to a specific type of diabetes [ 14 ]. Moreover, none of these studies have provided data on the clinical trajectory of new-onset diabetes cases or quantified the impact of COVID-19 as a risk factor for new-onset diabetes during the long COVID phase.…”
Section: Introductionmentioning
confidence: 99%
“…The TriNetX platform has been used extensively in both adult and pediatric patient populations to report epidemiological outcomes and risk assessments in an array of pathologic settings. 13 15 This study followed the Strengthening the Reporting of Observational Studies in Epidemiology reporting guidelines. 16 Description of the database is further laid out in the Supplemental Methods .…”
Section: Methodsmentioning
confidence: 99%
“…Their analysis revealed that the COVID-19 pandemic led to a 9.5% increase in global new-onset T1D cases among pediatric populations, the global number of children experiencing DKA and severe DKA increased by 9.5%, 25%, and 19.5%, respectively, when compared to pre-COVID-19 years [ 19 ]. In separate meta-analysis from other countries and time periods, it was also demonstrated that the risk of new-onset T1DM and DKA following COVID-19 infection in children and adolescents was higher compared to non-COVID-19 control groups [ 20 22 ].…”
Section: Epidemiologymentioning
confidence: 99%